Reference values of regional cerebral oxygen saturation during the first 3 days of life in preterm neonates (2015)
Background: Currently, reliable reference values of regional cerebral oxygen saturation (rScO2) for different gestational age (GA) groups are lacking, which hampers the implementation of near-infrared spectroscopy (NIRS) alongside monitoring arterial oxygen saturation (SaO2) and blood pressure in neonatal intensive care. The aim of this study was to provide reference values for rScO2 and cerebral fractional tissue oxygen extraction (cFTOE; (SaO2 ? rScO2)/SaO2) for small adult and neonatal NIRS sensors. Methods: In this study, 999 infants born preterm (GA <32?wk) were monitored with NIRS during the first 72?h of life. Mixed modeling was used to generate reference curves grouped per 2?wk of GA. In addition, the influence of a hemodynamically significant patent ductus arteriosus, gender, and birth weight were explored. Results: Average rScO2 was ~65% at admission, increased with GA (1% per week) and followed a parabolic curve in relation to postnatal age with a peak at ~36?h. The cFTOE showed similar but inverse effects. On average, the neonatal sensor measured 10% higher than the adult sensor. Conclusion: rScO2 and cFTOE reference curves are provided for the first 72?h of life in preterm infants, which might support the broader implementation of NIRS in neonatal intensive care.